Delignification of Cassava Peel by Using Alkaline Hydrogen Peroxide Method: Study of Peroxide Concentration, Solid/Liquid Ratio, and pH - Dini Nur Afifah; Neni Damajanti; Maulani Mustholidah; Hariyanti (Jurnal Teknik Kimia dan Lingkungan, 2022)
Cassava peel is a natural material with cellulose content reaching 33.33%. In order to utilize cassava peel as a biodegradable polymer and renewable energy alternative, a delignification process is essential to separate cellulose from hemicellulose and lignin, which prevents the penetration of cellulose hydrolyzer. The delignification method chosen in this study was alkaline hydrogen peroxide (AHP). The AHP is based on the autoxidation of lignin using hydrogen peroxide (H2O2) in an alkaline environment. This method was chosen because it can damage the lignocellulosic structure with relatively low energy and is more selective for lignin. However, under certain conditions, AHP can trigger carbohydrate depolymerization, which decreases yield. Therefore, it is necessary to study the effect of H2O2 concentration, Solid/Liquid ratio (S/L) (w/v), and pH to evaluate the effectiveness of lignin removal in cassava peel. The concentration of H2O2 was varied into 1.5%, 3%, 4.5%, 6%, and 7.5%. The S/L ratio is varied to 1:3, 1:5, 1:7, 1:9,1:12. The pH of the solution was varied to 8, 9, 10, 11, and 12. The reaction temperature was maintained at 70-90 °C for 3 hours. The results showed that lignin could be reduced to 84.05% for 3 hours by using 6% H2O2, an S/L ratio of 1:5, and a pH of 11. The reaction carried out under these conditions can also increase the amount of cellulose from 33.33% to 49.00%.